Impact of management models on revenue sharing for signaling medical equipment reliability. Issue 6 (3rd June 2022) - Chen, Yu-Hung; Kung, Ling-Chieh; Yu, Jiun-Yu; Tsai, Hsin-Jung; Wang, Yu Jen
Abstract: This paper examines the contracting problem between a medical equipment vendor and a hospital in the healthcare industry. Many medical treatments depend heavily on the reliability of newly developed equipment, which typically encompasses private information on the part of the vendor. We built a game-theoretic model to examine the optimal contract a vendor can offer to prevent hospitals from underpaying for a reliable machine. First, the contract format including revenue sharing may serve as a signaling device of reliability. Second, the management model of a hospital has a strong impact on contract design. In particular, the vendor is better able to signal its reliability through revenue sharing to a non-profit hospital than to a for-profit hospital. Lastly, revenue sharing becomes more attractive to vendors as hospitals are more concerned about social welfare.